Changes in jawbones of male patients with chronic renal failure on digital panoramic radiographs - Dagistan, Saadettin; Miloglu, Ozkan; Caglayan, Fatma (European Journal of Dentistry, 2016)
Objective: To compare the existence of gonial cortical bone thickness, antegonial index, mandibular canal bone resorption and gonial angle values and pathologies like ground-glass appearance in jawbones and brown tumor in male patients undergoing dialysis due to chronic renal failure and men from the healthy control group on panoramic radiographs. Materials and Methods: Panoramic radiographs were taken from 80 male individuals in total (40 normal and 40 dialysis patients). Values obtained from the right and left sides of the mandible were summed and their means were calculated. Gonial cortical thickness, antegonial index and gonial angle values were assessed with the Student's t-test, mandibular canal wall resorption with the Chi-square test, and pathologies such as ground-glass appearance and Brown tumor as “available” or “not available.” Results: Statistically significant differences were observed among the antegonial index (P < 0.001), gonial cortical bone thickness (P < 0.001), and gonial angle (P < 0.001) values of study and control groups. Besides, mandibular canal wall resorption (P < 0.001) was also statistically significant. In the study group, pathologies with ground-glass appearance were encountered in mandible, but no radiographic findings were observed similar to brown tumor. Conclusions: Compared to the control group, decreases were found in gonial cortical bone thicknesses, antegonial index values, mandibular canal wall resorption, and gonial angle values of the patients receiving dialysis treatment due to chronic renal failure. Although it is not statistically significant, pathology with ground-glass appearance was detected in a patient, but no pathologies like brown tumor were observed. These findings from patients with chronic renal failure must be evaluated in panoramic radiography.
Keywords: Brown tumors; chronic renal failure; dialysis; fibrous dysplasia; mandibular bone